Innovative low-risk maternity clinic. Family physicians provide care in Calgary. - Lane, C. A. (College of Family Physicians of Canada, 1997)
PROBLEM BEING ADDRESSED: Because some family physicians choose to stop providing maternity care, many women and their physicians have to seek this care from other providers. These providers must respect family physicians' relationships with patients and the necessity of returning the family to the referring physician for primary care after appropriate maternity and newborn care has been provided. OBJECTIVE OF PROGRAM: To design a clinic to address this problem and to deal with the practical issues, such as preservation of lifestyle, adequate remuneration, and avoiding litigation, family physicians face when they choose to practise obstetrics. To provide role models and training opportunities for future family physicians. MAIN COMPONENTS OF PROGRAM: Compatibility and cooperation among member physicians is essential in order to provide care to a substantial number of patients using an established protocol. A well-organized call schedule allows clinic physicians to enjoy a reasonable lifestyle. CONCLUSIONS: The clinic, established and organized by family physicians, provides family-centred maternity care for women and their families when their family physicians choose not to practise obstetrics.